PENGARUH ATONIK TERHADAP PERTUMBUHAN TUNAS PADA TURUS AKAR SUKUN (ARTOCARPUS ALTILIS (PARKINS.) FOSB.) - FACHRUROZI, Z.; HARAHAP, R. (Research Center for Biology-Indonesian Institute of Sciences, 1985)
Z. FACHRUROZI & R. HARAHAP 1985. The effect of atonic solutions on the growth of bread fruit (Artocarpus altilis (Park) Fosbere). Berita Biologi 3 (1)12-15, -A study on the application of atonic solution as the stimulating agent on the growth of bread fruit suckers indicated that the solution containing of 250 ppm and 500 ppm respectively are significantly increased the numbers as well as speeded up the growth of the 15 cm length suckers. The possibility to use these solutions on the suckers less than 15 cm length is discussed.